"Evaluation of Hand Absorpsiometry and Lumbar-Femoral Dual Energy X-Ray Absorptiometry in Postmenopausal Women" - Original Investigation - Canan Gücük Tezel; Nesrin Canik Baysal; Hicran Uşan; Ayşen Karabulut; Afitap İçağasıoğlu (Galenos Yayinevi, 2006)
The aim of this study is to evaluate the correlation and diagnostic value of digital radiographic absorptiometry and Dual Energy X-Ray Absorptiometry (DXA) in the diagnosis and assessment of osteoporosis.Spine and non-dominant femoral DXA measurements ( Lunar Cooperation, USA) and non-dominant hand absorptiometric measurements ( Metriscan-Alara, California-USA) have been done in 172 post-menopausal women who were outpatients in the Physical Therapy and Rehabilitation Clinic at İstanbul Göztepe Hospital of Education and Research. Demographic characteristics were identified. Statistical analyses have been performed by the calculation of Pearson correlation coefficient. The post-menopausal women mean age was 59±8.43Std (41-81 years). Both spine and femur DXA T scores were moderately correlated with radiographic absorptiometric scores (r: 0.63 and 0.62 respectively, p<0.001). Femoral and L1-L4 T scores were moderately correlated (r. 0.53,p<0.001). Different measurements methods of bone mineral density at different skeletal sites, in parallel to the literature, are moderately correlated in post-menopausal women. We can conclude that radiographic absorptiometry can be used as a screening technique or when DXA measurement is not available. (Osteoporoz Dünyasından 2006; 12 (1): 9-11)